Quintessence of personality aspects of entrepreneurship development - K, Selvakumar; Nagasubramaniyan, G. (Edelweiss Applied Science and Technology, 2026)
This study examines the role of personality dimensions in entrepreneurship development by analysing the relationship between entrepreneurs’ demographic characteristics and selected psychological variables. Drawing upon the interdisciplinary perspectives of psychology and entrepreneurship, the research investigates achievement motivation, internal locus of control, risk-taking propensity, role ambiguity, and role stress among entrepreneurs in Dharmapuri District, Tamil Nadu. A sample of 140 Micro, Small, and Medium Enterprise (MSME) entrepreneurs was selected through random sampling. Demographic variables such as age, educational qualification, family type, nativity, parental occupation, and gender were treated as independent variables, while psychological characteristics were considered dependent variables. Chi-square analysis revealed significant associations between several demographic characteristics and entrepreneurial personality traits. Achievement motivation was significantly related to age, education, family type, parental occupation, and gender. Internal locus of control showed significant associations with age, education, nativity, parental occupation, and gender. Risk-taking propensity was significantly influenced by age, education, parental occupation, and gender, while role ambiguity and role stress were associated with multiple demographic factors. The study concludes that personality characteristics are integral to entrepreneurial development and success. Understanding these psychological dimensions provides valuable insights for entrepreneurship promotion, training programs, and policy interventions aimed at fostering entrepreneurial growth and sustainability.